Chaos Analysis on the Acceleration Control Signals of the Piezoelectric Actuators in the Stewart Platform - Jiaqiang E; Cheng Qian; Teng Liu; Guanling Liu (Shock and Vibration, 2016)
In order to solve the nonlinear mechanism in the process of actual control application of six-degree-of-freedom parallel Stewart platform, the chaos theory was applied in the paper to analyze the acceleration control signal. The research included correlation dimension calculation by use of the G-P method, the maximum Lyapunov coefficient of the acceleration control signal, and Kolmogorov entropies of the acceleration control signal. The results show that the acceleration signals are of chaos characteristics, and there are lots of influencing factors to the acceleration variables.